Автоматизація визначення спрямованості порушень фізичного розвитку - Висоцька, О. В.; Друзь, В. А.; Доброродня, Г. С.; Довнар, О. С. (My University, 2018)
У роботі обґрунтовано актуальність автоматизації визначення спрямованості порушень фізичного розвитку з урахуванням індивідуальних особливостей людини. Обґрунтовано необхідність врахування соматотипу для визначення індивідуальної схильності організму до порушень фізичного розвитку. Сформовано семантичний простір росто-вагових відносин, який відображає якісну структуру будови соматотипу, що сприяє індивідуалізації виявлення порушень фізичного розвитку. Розроблено структурну схему концептуального представлення даних. В работе обоснована актуальность автоматизации определения направленности нарушений физического развития с учетом индивидуальных особенностей человека. Обоснована необходимость учета соматотипа для определения индивидуальной склонности организма к нарушениям физического развития. Сформировано семантическое пространство росто-весовых отношений, которое отображает качественную структуру строения соматотипа, что способствует индивидуализации определения нарушений физического развития. Разработана структурная схема концептуального представления данных. In this paper physical development impairment of urgency automation direction definition is based. Somatotype relevance for human body individual predisposition to physical development impairment assessment is grounded. The analysis of existing methods and software applications which leads to the objective of research, namely, the definition of physical development impairment direction is carried out. A three-dimensional-based structuring approach to structuring of biological zones from the images in human body has a number of advantages. We formed a semantic space of statural-weight value reflecting the somatotype qualitative composition, which is conductive to the developmental conditions individualization. We created a conceptual view of database flow chart for the automated system detection of developmental conditions patterns. The results obtained can be used in clinical medicine with an objective to the detection of somatotype predisposition to various pathologies. In addition, the results obtained can be used in human metabolic and functional disorders diagnostics and prophylaxis, and, as a consequence, in early functional disorders of human body prevention running into a disease.
Keywords: фізичний розвиток; маса тіла; соматотип; формоутворення